FTCS-23 the Twenty-Third International Symposium on Fault-Tolerant Computing
DOI: 10.1109/ftcs.1993.627312
|View full text |Cite
|
Sign up to set email alerts
|

The variation of software survival time for different operational input profiles (or why you can wait a long time for a big bug to fail)

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract-This paper provides experimental and theoretical evidence for the existence of contiguous failure regions in the program input space ('blob' defects). For real-time systems where successive input values tend to be similar, blob defects can have a major impact on the software survival time because the failure probability is not constant. For example, with a 'random walk' input sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
7

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 11 publications
2
63
0
7
Order By: Relevance
“…A more comprehensive study was conducted by Bishop (1993), who examined program faults in control functions for nuclear reactors. He found that virtually all the faults were "blob" faults -that is, each fault revealed failures in a contiguous region of the input domain.…”
Section: Failure Patternsmentioning
confidence: 99%
“…A more comprehensive study was conducted by Bishop (1993), who examined program faults in control functions for nuclear reactors. He found that virtually all the faults were "blob" faults -that is, each fault revealed failures in a contiguous region of the input domain.…”
Section: Failure Patternsmentioning
confidence: 99%
“…For example, the operational profile ) (x U has been introduced in various reliability models to handle the relative frequencies of inputs [28]. As another example, the EL and LM models use a random parameter  to describe the uncertainty in both software structures and residual faults, i.e.…”
Section: Failure Distribution (Fd) Modelmentioning
confidence: 99%
“…Experiments and theoretical justifications show the existence of contiguous failure regions in the program input space and that, for many applications, such as real-time control systems, the inputs often follow a trajectory of contiguous points in the input space. For these reasons the inputs which originate failures of the software are very rarely isolated events but more likely grouped in clusters [Amman88,Bishop93,Bishop88]. For all the classes of applications to which these considerations apply, analyses of software dependability performed assuming independence between successive iterations seem to lead to results excessively diverging from the real behaviour of the analysed system.…”
Section: Introductionmentioning
confidence: 99%